Engineering membrane asymmetry to increase medium‐chain fatty acid tolerance in Saccharomyces cerevisiae. Issue 1 (4th November 2021) - Liu, Hui; Yuan, Weijia; Zhou, Pei; Liang, Guangjie; Gao, Cong; Guo, Liang; Hu, Guipeng; Song, Wei; Wu, Jing; Chen, Xiulai; Liu, Liming
Abstract: Saccharomyces cerevisiae is an attractive chassis for the production of medium‐chain fatty acids, but the toxic effect of these compounds often prevents further improvements in titer, yield, and productivity. To address this issue, Lem3 and Sfk1 were identified from adaptive laboratory evolution mutant strains as membrane asymmetry regulators. Co‐overexpression of Lem3 and Sfk1 [Lem3(M)‐Sfk1(H) strain] through promoter engineering remodeled the membrane phospholipid distribution, leading to an increased accumulation of phosphatidylethanolamine in the inner leaflet of the plasma membrane. As a result, membrane potential and integrity were increased by 131.5% and 29.2%, respectively; meanwhile, the final OD600 in the presence of hexanoic acid, octanoic acid, and decanoic acid was improved by 79.6%, 73.4%, and 57.7%, respectively. In summary, this study shows that membrane asymmetry engineering offers an efficient strategy to enhance medium‐chain fatty acids tolerance in S. cerevisiae, thus generating a robust industrial strain for producing high‐value biofuels. Abstract : Engineering membrane asymmetry is a novel and efficient strategy for tuning the membrane functions in Saccharomyces cerevisiae . Co‐overexpression of Lem3 and Sfk1, two key membrane asymmetry regulators that were identified from adaptive laboratory evolution mutant strain, through promoter engineering remodeled the membrane phosphatidylethanolamine distribution and increased membrane integrity. By applying this strategy, an engineered S. cerevisiae strain exhibited improved stress tolerance to medium‐chain fatty acids.